Risk Factors for Refractory Diabetic Macular Oedema after Sub-Tenon’s Capsule Triamcinolone Acetonide Injection - Toshiyuki Oshitari; Yuta Kitamura; Sakiko Nonomura; Miyuki Arai; Yoko Takatsuna; Eiju Sato; Takayuki Baba; Shuichi Yamamoto (Journal of Ophthalmology)
The purpose of this study is to identify the risk factors for a recurrence or persistence of diabetic macular oedema (DME) after a sub-Tenon’s capsule triamcinolone acetonide (STTA) injection. The medical records of 124 patients (124 eyes) treated by STTA were reviewed. The age, sex, HbA1c level, best-corrected visual acuity, central macular thickness, insulin use, pioglitazone use, systemic hypertension, serous retinal detachment, proteinuria, panretinal photocoagulation, microaneurysm photocoagulation (MAPC), subthreshold micropulse diode laser photocoagulation (SMDLP), cataract surgery, and history of vitrectomy were examined by logistic regression analysis. Procedures of MAPC and SMDLP were significantly associated with DME treated with STTA (P=0.0315, P=0.04, resp.). However, a history of vitrectomy was found to have significantly fewer recurrences or persistent DME after STTA (P=0.0464). In conclusion, patients who required combined MAPC or SMDLP with a STTA injection had significantly higher refractoriness to STTA, but postvitrectomy may prevent the recurrence or persistence of DME after STTA injection.